Rāmacandrunihampīyātra : Vijayanagaraunnatyamunu guriñci vrāyambaḍina padyakāvyamu - Somayaji, G. J., 1900- (SAMP early 20th-century Indian books project ;, 1930)
On Hampi, site of ruined city of Vijayanagar, flourished from 1336-1575.